Strengthening The Skill of The Sri Tanjung Batik Community (KBT) through Eco-print Batik Innovation In Bangsring Village Wongsorejo Banyuwangi - Jauhar Ariful H, M.; Taufiq, Amal; Kamal, Faizul (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2024)
Abstract: Bangsring Village Wongsorejo is one of the village that has both tangible and intangible assets, one of the intangible assets is an organizational asset in the form of a batik community founded by women, but several years ago this community was passive so it needs to be reactivated by carrying out assistance to them in producing batik because around them there are other assets which are also very strategic in the form of leaves which are the main ingredient in eco-printing. This cammunity service uses the ABCD method which focuses on assets in the community, data mining techniques in the form of in-depth interviews and Focus Group Discussions. The main activity program in this cammunity service is strengthening the capacity of members of the Tanjung Sari batik group in the form of workshops and field practice. After carrying out the activities, community experienced changes in the knowledge aspect of producing eco-print batik, in attitudes, organizational and increase income.